2012
DOI: 10.2174/092986712799034914
|View full text |Cite
|
Sign up to set email alerts
|

Novel Biotransformation Process of Podophyllotoxin to 4 -Sulfur-Substituted Podophyllum Derivates with Anti-Tumor Activity by Penicillium purpurogenum Y.J. Tang

Abstract: According to the structure-function relationship of podophyllotoxin (PTOX) and its analogue of 4'- demethylepipodophyllotoxin (DMEP), the 4 β-substitution of sulfur-containing heterocyclic compounds with a carbon-sulfur bond at 4 position of PTOX or DMEP is an essential modification direction for improving the anti-tumor activity. So, four novel 4 β-sulfursubstituted podophyllum derivatives (i.e., 4β -(1,2,4-triazole-3-yl)sulfanyl-4-deoxy-podophyllotoxin (4-MT-PTOX), 4β-(1,3,4- thiadiazole-2-yl)sulfanyl-4-deox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…In addition, the expression of TUBB3 (a key member of β-tubulin) and TOPIIA (a key nuclease in DNA replication) was inhibited in tumor cells after MPTOX treatment. Furthermore, Bai et al (2012) and Zhao et al (2015Zhao et al ( , 2019) demonstrated that the carbon-sulfur bond at the 4-position (C-4) of the carbon ring of PTOX reduced the inhibitory effect of dose on tubulin polymerization, thereby enhancing its therapeutic effect. They synthesized 4β-NH-(6aminoindole)-4-deoxy-PTOX Compound 25 (Figure 7) that can target the α-tubulin binding site and colchicine binding domain, as confirmed by X-ray crystallographic analysis.…”
Section: Main Mechanismmentioning
confidence: 99%
“…In addition, the expression of TUBB3 (a key member of β-tubulin) and TOPIIA (a key nuclease in DNA replication) was inhibited in tumor cells after MPTOX treatment. Furthermore, Bai et al (2012) and Zhao et al (2015Zhao et al ( , 2019) demonstrated that the carbon-sulfur bond at the 4-position (C-4) of the carbon ring of PTOX reduced the inhibitory effect of dose on tubulin polymerization, thereby enhancing its therapeutic effect. They synthesized 4β-NH-(6aminoindole)-4-deoxy-PTOX Compound 25 (Figure 7) that can target the α-tubulin binding site and colchicine binding domain, as confirmed by X-ray crystallographic analysis.…”
Section: Main Mechanismmentioning
confidence: 99%
“…The numbers of triazoles fused to thiadiazoles exhibit various therapeutically important property probably due to the existence of N-C-S fragment in ring. Literature survey has revealed that the 6-amino thiadiazole structure plays vital role in biologically active compounds consequently represents fascinating moiety for therapeutic chemistry.1,3,4thiadiazoles are vital classes of azoles with significant pharmacological activities such antimicrobial [1][2][3][4][5][6] , antioxidant 7 , antituberculosis 8 , anticancer [9][10][11] , analgesic 12 , anti-inflammatory 13 , antiviral [14][15] , antifungal [16][17][18][19] , antitumor 20 , urease inhibitor 21 , analgesic and anti-inflammatory 22 , antidepressant 23 , anticonvulsant 24 , antimycotic 25 , diuretic 26 , cytotoxic 27 , corrosion inhibition effect 28 , antiproliferative 29 , anthelmintic 30 . Moreover, nowadays researchers desire to yield fused or hybrids of various heteroatom ring to improve the medicinal property.…”
Section: Introductionmentioning
confidence: 99%
“…The microtubules in tumor cells are heterodimers composed of α- and β-tubulins. Microtubule damage can induce cell cycle arrest at the G 2 /M stage and lead to formation of abnormal mitosis spindle, which can ultimately lead to cell apoptosis. Additional research on drug design, biosynthesis, and structural modification with tubulin as the target site are current ongoing projects. Natural products are an excellent source for many active compounds, including microtubule-targeting compounds.…”
Section: Introductionmentioning
confidence: 99%